Pengaruh Hambatan Samping Terhadap Kinerja Ruas Jalan Akibat Aktivitas Pasar - Ikhlal, Khairul Al; Djuniati, Sri; Sebayang, Mardani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Traffic problems that often happens in Pekanbaru is congestion, which are population growth and vihicles are not supported with traffic and infrastructure developments. Factor that cause this congestions is effect of side barriers that can reduce capacity of the roads Side obstacle factors are: pedestrians, vehicle stop / parking on the road, vehicle exit / entry road and slow vehicle. The study was conducted in three market locations by taking direct data of field, for traffic volume, side barrier and vehicle speed then analyzed by using Manual of Capacity of Road Indonesia (MKJI) 1997.Research result showed that traffic volume of Tuanku Tambusai street in front of Cik Puan market on east is 3092 smp/hour with a capacity of 3871 smp/hour, degree of saturation 0.80 and on west, traffic volume is 3034 smp/hour, with a capacity of 3871 smp/hour, degree of saturation is 0.78. H.R Subrantas street in front of Pasar Pagi Panam on east is 2250 smp/hour, with a capacity of 2915 smp/hour, degree of saturation is 0.77 and on west, traffic volume is 2275 smp/hour, with a capacity of 2915 smp/hour, degree of saturation 0.78 and Durian street in front of Palapa market, the traffic volume is 1929 smp/hour, with a capacity of 2581 smp/hour, degree of saturation is 0.75. Based on the result of contribution analysis of side barrier at the three research sites, that the most effective way is doing by omitting the sides obstale factor of vehicle out into the side of the road and side obstale factor vehicle parking/stop at the road body and vehicles in and out in the side of the road.Keywords: Side Barriers, Volume, Capacity, Market activity, Degree of Saturation .